Cervical Subcutaneous Emphysema following Total Laryngectomy: An Unusual Complication of Nasogastric Intubation. (7th July 2019) - Jama, Guled M.; Barmayehvar, Behrad; Vydianath, Sanjay; Mathews, John; Spinou, Catherine
Abstract : The nasogastric tube remains an important route of enteral feeding in the early postoperative period following total laryngectomy. Its insertion, however, is not without any risks of complications. In this article, we report an unusual case of inadvertent nasopharyngeal perforation secondary to intraoperative nasogastric tube insertion presenting as unilateral cervical subcutaneous emphysema in a patient who underwent total laryngectomy.